Dampak UU HPP (Harmonisasi Peraturan Perpajakan) Pasca PP 23 Pada UMKM di masa Pandemi Covid – 19 - Tri Ega Nurillah; Isnani Yuli Andini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to understand the impact of the HPP Law (Harmonization of Tax Regulations) after PP 23 on MSMEs during the Covid-19 Pandemic. In this research use qualitative research. Data collection techniques using interview techniques as well as observation and documentation. The results showed that after the researchers conducted an analysis of the HPP Law on three MSMEs in Sumenep Regency during the Covid-19 Pandemic, where two of the informants said it had a negative impact because they felt they did not receive sociealization where their business locations were far from the city and were also ignorant and One resource person said that it had a positive impact because this resource person, although he did not know the impact of the HPP Law, said he thought it would help MSME actors in overcoming economic problems with the HPP Law policy.